2004
DOI: 10.1002/em.20009
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and mitomycin C‐induced micronuclei in peripheral blood reticulocytes from severely malnourished rats

Abstract: Severe malnutrition caused by deficiencies in protein, calorie, and micronutrient intake is widely distributed throughout the world and is a particular problem in developing countries. Animal models have been useful for studying the effects of malnutrition under different experimental conditions. In this study, we have evaluated the effect of malnutrition on the frequency of spontaneous and mitomycin C (MMC)-induced micronuclei in the peripheral blood of rats measured using a flow cytometric analysis technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
0
8
0
5
Order By: Relevance
“…The pups' day of birth was calculated once pregnancy was confirmed. After delivery, five newborn pups per mother were randomly selected for homogeneity among the groups and to assure appropriate offspring feeding [21, 22]; a total of 25 pups per group were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…The pups' day of birth was calculated once pregnancy was confirmed. After delivery, five newborn pups per mother were randomly selected for homogeneity among the groups and to assure appropriate offspring feeding [21, 22]; a total of 25 pups per group were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Considerable variability in the percentage of RETs in the peripheral blood of rats has been reported in previous studies [Ortiz et al, 2004]. The relatively high level of RETs in both groups of rats in our study may be related to their young age (21-day-old or 3-week-old rats).…”
Section: Discussionmentioning
confidence: 44%
“…Another study has shown that spleen lymphocytes from UN rats during lactation have increased MN frequencies [Ortiz et al, 1995]. Furthermore, protein-calorie malnutrition experimentally produced during lactation increases the frequencies of spontaneous and MMC-induced MN-RETs in rat peripheral blood [Ortiz et al, 2004].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this case, comparison of the study data to the negative historical control data indicates that the statistically signifi cant result produced by the trend test is not indicative of a biologically relevant response to drug treatment. With regard to biological relevance and interpretation of results, it is also worth noting that a number of confounding factors have been demonstrated to induce increases in micronucleated erythrocytes including hypothermia [54,55] , induction of hematopoiesis [56] , and malnutrition [57] .…”
Section: Data Analysis and Interpretation Of Resultsmentioning
confidence: 99%